THE PSYCHOLOGICAL IMPACTS OF SEXUAL OFFENCES TOWARDS WOMEN IN SOUTH AFRICA - Linda Moloko Soemane (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
South Africa has one of the highest rates of sexual offences globally, making it a critical site for understanding the psychological effects of sexual offences trauma. This scoping review aims to explore the psychological consequences of sexual offences on women in South Africa. Using the methodology framework by Arksey, H and O'Malley, L (2005), this qualitative scoping review found about 17 652 articles from science direct and google scholar database of which only 10 articles met the eligibility criteria and 112 online newspaper articles from google search of which only 10 articles met the eligibility criteria with an emphasis on the South African context. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) together with the inductive Thematic Content Analysis (TCA) were used to analyse the data. The study findings indicate that sexual offences expose women to various psychological effects both short-term and long-term consequences. This study revealed that victims of sexual offences experience intensive and varied psychological impacts such as Post-Traumatic Stress Disorder (PTSD), depression, suicidal thoughts, self-blame, shame, anger, sexual dysfunction, emotional suppression and sleep disturbances. It also highlights the ways in which societal stigmatisation and misconceptions of sexual offences intersect with the indicated psychological effects, often exacerbating the challenges faced by victims. The review emphasises the role of stigma and victim-blaming in prolonging the trauma experienced by victims. Further research is recommended to explore the long-term psychological effects of sexual offences and effectiveness of interventions programmes designed to help victims in their recovery journey.